2019
DOI: 10.1111/joss.12528
|View full text |Cite
|
Sign up to set email alerts
|

Partial projective mapping and ultra‐flash profile with and without red light: A case study with white wine

Abstract: Partial projective mapping (PM) is a sensory method that is used to evaluate one sensory modality (flavor, texture, or appearance). The objective of the study was to determine if the use of red light to mask subtle differences in the colors of the wine influenced the consumers' flavor descriptions of white wines. The results of partial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The second dimension also separated W2 (L'Acadie) from W1 (L'Acadie) and W3 (Seyval Blanc). The attributes identified by the participants agree with past studies investigating white wines produced in NS (Hayward, Finlay, et al, 2020; Hayward, Jantzi, Smith, & McSweeney, 2020; Smith & McSweeney, 2019). Also, it is clear from the results that the panelists were able to separate the different varieties of wine.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The second dimension also separated W2 (L'Acadie) from W1 (L'Acadie) and W3 (Seyval Blanc). The attributes identified by the participants agree with past studies investigating white wines produced in NS (Hayward, Finlay, et al, 2020; Hayward, Jantzi, Smith, & McSweeney, 2020; Smith & McSweeney, 2019). Also, it is clear from the results that the panelists were able to separate the different varieties of wine.…”
Section: Resultssupporting
confidence: 87%
“…Participants were then asked to complete a CATA questionnaire. The descriptors included in the CATA questionnaire were based on past studies evaluating white wines produced in NS (Barton, Hayward, Richardson, & McSweeney, 2020; Smith & McSweeney, 2019) and evaluations by research assistants who are experienced in sensory analysis (sweet, apple, bitter, aftertaste, no aftertaste, berry, watery, fruity, citrus, acidic, earthy, sour, honey, oak, pear, floral, dry, tree fruit, yeasty, vegetal). To account for possible CATA attributes order bias, terms were randomized based on the procedure suggested by Meyners and Castura (2016).…”
Section: Methodsmentioning
confidence: 99%
“…One limitation of this study is that we did not replicate the study with another set of panels nor with the same panel at a later period of time. Smith and McSweeney (2019) showed that altering the physical surroundings (standard vs. red lights) altered the projective mapping by consumers, which suggests that findings could change depending on factors extrinsic to the samples.…”
Section: Discussionmentioning
confidence: 99%
“…This practice can show that by learning how to taste for example wines, even novices can come to appreciate better and more interesting wines. It is the interplay between tasting and knowing that leads to refined discrimination and a better understanding of the wine [31].…”
Section: Panelist Selection Monitoring and Product-specific Testsmentioning
confidence: 99%